PEMANFAATAN BANGUNAN BERSEJARAH SEBAGAI WISATA WARISAN BUDAYA DI KOTA MAKASSAR - Rafika Hayati (JURNAL MASTER PARIWISATA, 2014)
Colonial period in Indonesia bequeathed a number of buildings such as schools, bank and offices. The buildings have nuance of Dutch architecture, therefore becoming cultural heritages and tourist attractions. The Aim of this research is to find out the historical buildings utilization in Makassar city, South Sulawesi Province, however in this research selected three bulidings which developed as heritage tourism, namely Fort Rotterdam, Museum Kota dan Gedung Kesenian Makassar. The three historical buildings selected as research location because of the physical potency is building architecture which completed with non physical potency is historical and cultural value. This research applied tourist attraction management, tourism area life cycle by Butler and tourism marketing theory to find out evolution life cycle of each buildings then arrange the effective strategy to develop Fort Rotterdam, Museum Kota and Gedung Kesenian as heritage tourism in Makassar city.The article argues that the utilization of Fort Rotterdam as a tourist attraction is classified into development phase. Fort Rotterdam has been renovated several times by developing La Galigo Museum inside to increase the attractiveness. Local government has also a lot of promotions. Museum Kota and Gedung Kesenian Makassar are classified into exploration phase since the two historical buildings need physical improvement, structuring showroom and facilities to handle collections of Museum Kota and the assurance of building management and maintenance of Gedung Kesenian. Based on the result of the research Fort Rotterdam, Museum Kota dan Gedung Kesenian Makassar do not only have physical potency of building and historical value but also to become interesting tourist attraction which need improvement by maintaining architecture identity as much as possible, providing supporting facilities needed by tourists and increasing promotion by local government.